Much ado about nothing [videorecording (DVD)] - Doyle, Patrick, 1953- (Metro Goldwyn Mayer Studios ; Distributed by Twentieth Century Fox Home Entertainment, 2009)
With his wedding a week away, Claudio can't wait to marry the beautiful young Hero. To distract him, his best friend Don Pedro devises mischief: a romantic trap for the sharp-tongued Beatrice and the man she loves to hate, Benedick. Their amusement is almost spoiled by the jealous scheming of Don John, but love and laughter prevail when the local constable unwittingly exposes the plot--and all the trouble proves to be much ado about nothing (111 min.).